PENGARUH INVESTMENT OPPORTUNITY SET, KEPEMILIKAN MANAJERIAL, DAN SUSTAINABILYTY ACCOUNTING TERHADAP NILAI PERUSAHAAN - Wahyu Agustini; Komang Fridagustina Adnantara; Made Yudi Darmita (Universitas Triatma Mulya, 2023)
This study aims to obtain empirical evidence regarding the effect of investment opportunity sets, managerial ownership, and sustainability accounting on firm value in manufacturers listed on the Indonesia Stock Exchange in 2019-2021 because several previous studies have shown inconsistent results. The value of the company is very important because it can affect the perception of investors towards the company so that the company will have more convenience in obtaining funds from investors. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sampling technique in this study used a purposive sampling method so as to get 19 companies as a research sample with a total of 57 companies. The data analysis technique used in this study uses multiple linear regression. The test results show that the investment opportunity set has an effect on firm value. Managerial ownership affects the firm value. Sustainability accounting affects the firm value.